2015
DOI: 10.4014/jmb.1501.01075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glucose Dehydrogenase and Pyrroloquinoline Quinine (pqq) Mutagenesis that Renders Functional Inadequacies in Host Plants

Abstract: The rhizospheric zone abutting plant roots usually clutches a wealth of microbes. In the recent past, enormous genetic resources have been excavated with potential applications in host plant interaction and ancillary aspects. Two Pseudomonas strains were isolated and identified through 16S rRNA and rpoD sequence analyses as P. fluorescens QAU67 and P. putida QAU90. Initial biochemical characterization and their root-colonizing traits indicated their potential role in plant growth promotion. Such aerobic system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…The biochemical pathways and genetics of PQQ-GDH synthesis and expression have been studied in many bacteria [32,41,42]. Van Schie et al [42] showed that the synthesis of PQQ-GDH holoenzyme and the PQQ cofactor could be non-coordinated and the control of PQQ-GDH activity by PQQ synthesis maybe widespread among bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical pathways and genetics of PQQ-GDH synthesis and expression have been studied in many bacteria [32,41,42]. Van Schie et al [42] showed that the synthesis of PQQ-GDH holoenzyme and the PQQ cofactor could be non-coordinated and the control of PQQ-GDH activity by PQQ synthesis maybe widespread among bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…QAU-92 (Table 1). PCR was carried out according to the procedure described by Naveed et al (2015). The amplified PCR products were sequenced commercially from LGC genomics (Germany) and compared with already published sequences in NCBI GenBank databases.…”
Section: Identification Of Isolate and Amplification Of Pqq Operonmentioning
confidence: 99%
“…To induce mutation in the pqq operon, the pqq biosynthesis "pqqC" was targeted for site directed mutation using PCR based knock out method (Naveed et al 2015) as described for QAU-92. The deletion plasmid of Pseudomonas spp.…”
Section: In Vivo Cloning and Site-specific Mutagenesis And Phosphate Solubilizationmentioning
confidence: 99%
“…Novel allyl PQQ combination with chlorogenic acid and methyl gentisate is found effective for hyper pigmentation acknowledged at diminution of skin hyper pigmentation (Gold; jhskincareclinic.co.uk).Loss of PQQ causes a reduction in connective tissue growth and repair proved by Cellular studies on fibroblasts leading to friable skin, loss of elasticity and connective tissue health also used in makeup and creams for aging and skin care etc. PQQ contributes on epidermal water dissipation, skin moisture, texture, viscoelasticity, and reduction in mast cell quantity in the dermis and epidermis and quantity of CD3⁺ T-cells giving improved skin barrier and function (Table 2) [112]. PQQ causing biological aging induced by ultraviolet A UVA in dermal fibroblasts of humans HDFs via ant apoptotic SIRT1-SIRT6-HO-1 and Nrf2 signaling pathways [113].…”
Section: Pqq Role In Skinmentioning
confidence: 99%